2016
DOI: 10.1016/j.pjnns.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Stent-assisted embolization of wide-neck anterior communicating artery aneurysms: Review of consecutive 34 cases

Abstract: The use of stent is feasible and effective for coil embolization of wide-necked anterior communicating artery aneurysms. Although periprocedural complications resulting in severe morbidity are rare, they should be noted, since in terms of thromboembolic events some of them presumably have a potential to be avoidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The stent-assisted coil embolization technology helps to stabilize the coils in the aneurysm, and contributes to the treatment of complicated intracranial aneurysms [ 2 ]. Although many studies have confirmed its effectiveness and feasibility, the rare complications during perioperative period are still worth noting [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stent-assisted coil embolization technology helps to stabilize the coils in the aneurysm, and contributes to the treatment of complicated intracranial aneurysms [ 2 ]. Although many studies have confirmed its effectiveness and feasibility, the rare complications during perioperative period are still worth noting [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a clinically silent coil prolapse presented in the case of our database no interventional treatment was initiated. Because the blood flow in the parent artery was maintained we decided to treat the patient conservatively with aggressive antiplatelet therapy, as was presented in previous reports [35,36]. The clinical and radiographic course of our patient with 20-month follow-up proceeded uneventfully, suggesting that the expectant management is likely to be a safe treatment option for non-massive coil protrusions in small MCA aneurysms.…”
Section: Discussionmentioning
confidence: 65%
“…Others include, coil migration, stent migration, stent thrombosis and delayed aneurysm rupture [9], however these complications are rare. Kocur et al [17] reported 2.9% (n = 1/34) periprocedural complication. This was related to prolonged retrieval of migrated coil in the anterior cerebral artery with consequent large infarction.…”
Section: Discussionmentioning
confidence: 96%